The impact of the new doctrine of the legal status of sociosubjects on the development of forensic coun-termeasures of the crimes - Ланцедова, Юлія Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The article describes the essence of the new doctrine of the legal status of sociosubjects. The essence of the legal status of sociosubjects’ balance new doctrine, which consists of a number of interrelated partial doctrines and concepts, is disclosed: 1. The composition of the sociosubjects (the individuals, the legal entities, the state, the interstate institution). 2. The composition of the legal status of sociosubjects (the rights, the freedoms, the responsibilities, the interests; the definition of each of these categories is proposed). 3. The internal balance of the legal status of sociosubjects, when the rights, freedoms and interests of certain sociosubject must justify the appearance of the appropriate volume of his duties. 4. The external balance of the legal status of sociosubject as a legal status of sociosubject should be the same with the other legal status of sociosubject of the same level and type. 5. The illogicality of the rights, freedoms, responsibilities and interests of the one of sociosubject at the expense of the legal status of other sociosubject. On this basis main constitutional duty of the state and some basic principles of the criminal proceedings is improved. The principle of perfection of the antycriminal proceeding should be viewed as a system of checks and balances, as a coherent action of these three partial principles of the antycriminal litigation: 1. The rationalization (optimization) of the antycriminal proceedings. 2. The efficiency of the antycriminal proceedings. 3. The quality of the antycriminal proceedings (absence of its other flaws, when the main indicator is an unconditional assignment of all the tasks concerning recognition, support and restoration of the legal status, violated by an offense, of all subjects of the antycriminal proceeding). The influence of the new doctrine of legal status of sociosubjects on development of the criminalistical tools of combating of the crimes is accentuated. The possibility of improving the criminalistic tactics of some practical actions that are to be carried out exclusively within the new doctrine of the legal status of sociosubjects and the principle of excellence of the antycriminal proceedings are disclosed.